Analisis Pengaruh Pengetahuan Kewirausahaan dan Lingkungan Keluarga Terhadap Minat Berwirausaha Mahasiswa FKIP Universitas Riau - Fransiska Mulyani Sucipto; Sumarno Sumarno; Filma Alia Sari (Jurnal Paedagogy, 2022)
This study aims to analyze the influence of entrepreneurial knowledge and family environment on the entrepreneurial interest of FKIP Riau University students. This research method used a quantitative approach. The population in this study were FKIP Riau University students who had taken entrepreneurship courses, with a total of 1,278 students. The sample of this study amounted to 93 students using a proportional random sampling technique. Instruments in this study used documentation and questionnaires. Data were analyzed by multiple linear regression analysis. The results showed that entrepreneurial knowledge and family environment had a positive and significant effect on the entrepreneurial interest of FKIP Riau University students, with a coefficient of determination (R2) of 57.7%. Moreover, the partial test results showed that entrepreneurial knowledge with a t-count (3.180) was greater than the t-table ( 1.986). The significance value was smaller than 0.05, which is 0.002. It indicated that the better the entrepreneurial knowledge obtained, the higher the interest in entrepreneurship in students and the family environment with a t-count (10.362) greater than the t-table (1.986) and the significance value smaller than 0.05, i.e. 0.000. It indicated that the greater the support from the family environment, the greater the student's interest in entrepreneurship.